Development of Innovative Executive Programme: Imam Profesional - Sulong, Muhammad Suhaimi; Zainol, Nur Zainatul Nadra; Mohammad, Che Adenan; Norizan, Siti Nur Akmal (Journal of Quranic Sciences and Research, 2024)
The Professional Imam Executive Program, the only academic program in Malaysia provides an opportunity for the community to improve knowledge, skills, and abilities for the duties of an imam, along with mosque and community management through a systematic lifelong learning process and becoming an excellent imam in guiding the Muslim community. Thus, Institut Ahli Sunnah Wal Jamaah (iSWAJ), Universiti Tun Hussein Onn Malaysia (UTHM) has developed such a programme since 2016 together with the Department of Islamic Religious State of Johor (JAINJ) and has graduated almost 70 students starting the first intake in 2018. The structure of this new program is designed to meet the demands and needs of the Mosque Management Division, JAINJ and to meet the gaps in the Imam's needs. This programme has four modulars – Tawhidic Foundation, Revelation Sciences, and Mosque and Community Management, and concluded with a Community Project that has been developed. Each modular cover three modules by itself. Those who attain 80 marks (A grade) and above from all modules in each modular will receive a Sijil Kemahiran Agama (Religious Skill Certificate) from the Johor State Islamic Religious Department (JAINJ), the only special award certificate to students of Imam ProfesionalTM. This innovative executive program is recognized by Johor Islamic Religious Council (MAIJ) and can be credited to prior experience-based learning (APEL). It will continue to accept applicants nationally and internationally for future intake and certainly offer many benefits for itself and the community.